Intergenerational differences in the experiences of middle-class Iranian migrant women post-revolution (1979) who are living in the UK - Salimi, Gita (2013)
The focus of this research is on well educated, middle-class Iranian migrant women who left their homeland at least ten years ago and are now living in the UK. The purpose of this research is to consider the first generation (who individually decided to migrate to the UK) and the second generation (the daughters of the first generation who had no other choice but to live in the country that their parents had selected) of Iranian migrant women according to intergenerational differences in their experiences of the migratory process. This study explores how Iranian women migrants (first and second generation) understand their gender roles in their homeland (Iran) and in their host country (Britain), therefore mapping the impacts of migration onto their gendered subjectivities.